The Effect of Combination of Natural Sound Music Therapy and Chamomile Aromatherapy on Anxiety in Pre-Cataract Surgery Patients - Masmirawati, Puput; Mugianti, Sri; Arif, Taufan; Hamarno, Rudi (Indonesian Journal of Applied Health, 2025)
Anxiety is usually experienced by preoperative patients. Cataract surgery is one of the stressors for pre-cataract surgery patients. Preoperative anxiety if not treated appropriately will be fatal to the surgical procedure. The purpose of this study was to determine the effect of a combination of natural sound music therapy and chamomile aromatherapy on the anxiety of cataract preoperative patients. The research design uses "quasi-experimental". The sampling method used purposive sampling with 36 respondents divided into 2 groups. The data analysis test uses univariate analysis to determine the characteristics of respondents. Bivariate analysis using paired t-test and independent t-test to determine the difference between 2 groups. The results of the independent t-test on the control group post test and treatment post test obtained a sig value. (2-tailed) 0.001, indicating a significant difference. The combination of nature sound music therapy and chamomile aromatherapy can reduce anxiety; nature sound music stimulates the limbic system to create a sense of calmness, while chamomile aroma stimulates the thalamus to release serotonin, thus reducing anxiety.